ANALYZING HOTS (HIGH ORDER THINKING SKILL) IN SOCIAL SCIENCE MID SEMESTER TEST AT GRADE IV - Hastuti; Rosleny Babo; Muhammad Nawir (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The reason for doing this research was the lack of teacher’ ability to design HOTS questions and factors that hindered the teacher in designing mid semester test questions. This research utilized a descriptive method with a qualitative approach. Based on the results of the analysis, it was revealed that 31 items did not fulfill the criteria for developing HOTS (High Order Thinking Skills). This research found that those 31 items contained 0% HOTS and 100% LOTS, indicating that the questions could not measure students' critical thinking skills. Thus, the teacher's ability in designing HOTS (High Order Thinking Skills) questions was categorized as Very Poor, and the teacher needed guidance to design HOT questions.